2012
DOI: 10.1186/1475-2875-11-310
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-reported use of sulphadoxine-pyrimethamine intermittent presumptive treatment during pregnancy (IPTp): a cross-sectional study

Abstract: BackgroundMalaria in pregnancy is a major health problem that can cause maternal anaemia, stillbirth, spontaneous abortion, low birth weight and intra-uterine stunting. The WHO recommends use of sulphadoxine-pyrimethamine (SP) for intermittent preventive treatment of malaria during pregnancy (IPTp) in endemic areas. Towards monitoring and assessing IPTp coverage in the population, the Roll Back Malaria Partnership recommends the use of self-reported data. The aim of this study was to assess the validity of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…However, in case of stock-outs of SP, pregnant women tend to purchase SP from private community pharmacies, and this may go undocumented [29]. Indeed documented uptake of IPTp-SP is in the ANCs is reported to be more reliable than self-reporting by pregnant women [36]. Detection of SDX at delivery predicts the exposure of pregnant women to SP that was used especially within the wash out period of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, in case of stock-outs of SP, pregnant women tend to purchase SP from private community pharmacies, and this may go undocumented [29]. Indeed documented uptake of IPTp-SP is in the ANCs is reported to be more reliable than self-reporting by pregnant women [36]. Detection of SDX at delivery predicts the exposure of pregnant women to SP that was used especially within the wash out period of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike in our health facility study, household surveys rely on self reports from pregnant women. A recent study from Uganda on the validity of pregnant women’s reported behaviour on taking doses of IPTp-SP showed such data to be inaccurate when assessed against plasma levels of sulphadoxine [43].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that none of the samples turned out positive suggests that participant selection in the control arm was done reasonably well. This scenario contrasts with a previous study in which up to 25% of pregnant women reporting nonuse of SP were found to have residual drug when tested [34]. Many previous studies reporting ineffectiveness of SP-IPTp have relied on self-reports and ANC records as proof of SP use [14, 15, 19].…”
Section: Discussionmentioning
confidence: 77%
“…To be eligible for enrollment, a woman had to have reported nonuse of SP-IPTp during the present pregnancy. As such claims may lack credibility for several reasons [34], each woman was required to provide a venous blood sample (4 mL) for detection of sulphadoxine (SDX). This requirement allowed for a retrospective assessment of SP exposure over the previous 2-3 months.…”
Section: Methodsmentioning
confidence: 99%